Perceptions of outdoor gymnasiums in National Capital Region, India: creating active environments for health promotion. (26th April 2020) - Sharma, Rachit; Chaudhary, Monika
Abstract: The prevalence of physical inactivity in India is estimated to be at 34%, the highest among South Asian nations. Interventions, such as outdoor gymnasiums/gyms, aiming to promote physical activity, are becoming popular worldwide, including in India. This paper presents the first empirical evidence on outdoor gyms in India from a qualitative perspective. Semi-structured, in-depth interviews of 56 outdoor gym stakeholders—40 users, 10 non-users, 4 healthcare providers and 2 outdoor gym implementing municipality authorities were conducted in the National Capital Region of India. The interviews were transcribed and analyzed through the Framework Method. The qualitative findings present the perceived benefits, barriers/challenges to using and provide insights for further improving and scaling up outdoor gyms in India. Health enhancement in the form of improved general fitness, body weight control and diversification of physical exercise routines, social connectivity, easy accessibility, affordability, green outdoor surroundings, and a place of intrigue and attraction in respective parks were the major reported benefits of outdoor gyms. Low gym equipment to user ratio was one of the major challenges to gym use across the user group. Healthcare providers and non-users were majorly concerned about the potentially incorrect and unsupervised use of outdoor gym equipment. Major suggestions for improvement were increasing the number of equipment installed, regular equipment maintenance, and the presence of an on-site physical exercise trainer. Outdoor gymnasiums present as a viable option for promoting physical activity and should be scaled up systematically to improve the health of the populations across India and other similar nations.